Analytical methods for the determination of oil carryover from CNG/biomethane refueling stations recovered in a solvent. Issue 20 (24th March 2020) - Arrhenius, Karine; Fischer, Andreas; Büker, Oliver; Adrien, Hervé; El Masri, Ahmad; Lestremau, Francois; Robinson, Tim
Abstract : Vehicle gas is often compressed to about 200 bar at the refueling station prior to charging to the vehicle's tank. Abstract : Vehicle gas is often compressed to about 200 bar at the refueling station prior to charging to the vehicle's tank. If a high amount of oil is carried over to the gas, it may cause damage to the vehicles; it is therefore necessary to accurately measure oil carryover. In this paper, three analytical methods for accurate quantification of the oil content are presented whereby two methods are based on gas chromatography and one on FTIR. To better evaluate the level of complexity of the matrix, 10 different compressor oils in use at different refueling stations were initially collected and analysed with GC and FTIR to identify their analytical traces. The GC traces could be divided into three different profiles: oils exhibiting some well resolved peaks, oils exhibiting globally unresolved peaks with some dominant peaks on top of the hump and oils exhibiting globally unresolved peaks. After selection of three oils; one oil from each type, the three methods were evaluated with regards to the detection and quantification limits, the working range, precision, trueness and robustness. The evaluation of the three measurement methods demonstrated that any of these three methods presented were suitable for the quantification of compressor oil for samples. The FTIR method and the GC/MS method both resulted in measurement uncertainties close to 20% rel. while the GC/FID method resulted in a higher measurement uncertainty ( U = 30% rel.).